Incidence and Risk of Fatal Adverse Events in Cancer Patients Treated With Vascular Endothelial Growth Factor Receptor 2-Targeted Agents: A Meta-Analysis With Trial Sequential Analysis of Randomized Controlled Trials - Zhao, Bin; Zhao, Hong; Zhao, Jiaxin (Frontiers in Medicine, 2019)
Background/Aim: Agents targeting vascular endothelial growth factor (VEGF) pathway have dramatically improved the outlook of cancer treatment. Meanwhile, it is well-known that they are associated with increases in the risk of fatal adverse events (FAEs). Vascular endothelial growth factor receptor 2 (VEGFR2)-targeted drugs have been approved for the treatment of several malignancies since 2014. However, little is known regarding the FAEs induced by VEGFR2-targeted agents across different tumor types and treatment regimens. Methods: We searched PubMed and Embase database from January 1966 to April 2018 for randomized controlled trials (RCTs) to calculate the incidence and relative risks (RRs) of FAE. Results:17 RCTs involving 6982 subjects with solid tumors were included in this study. The overall incidence of FAEs associated with VEGFR2-targeted agents was 1.7% (95% CI: 0.9%-2.4%). Compared with controls, the administration of VEGFR2-targeted agents did not increase the risk of FAEs (RR, 1.29; 95% CI, 0.90-1.86). No significant association was found between FAE and VEGFR2-targeted agents in subgroup analysis based on tumor type, treatment strategy, clinical phase, masking method, median treatment duration, and approval status. Additionally, FAEs occurred in the major organ systems dispersely. Trial sequential analysis revealed that our results are solid and further studies are unlikely to change it. Conclusions: VEGFR2-targeted agents were not associated with an increased risk of FAEs.